Youth pre-pandemic executive function relates to year one COVID-19 difficulties - Aizza, Alice; Porter, Blaire M.; Church, Jessica A. (Frontiers in Psychology, 2023)
Introduction The first year of the COVID-19 pandemic presented a series of stressors that could relate to psychological difficulties in children and adolescents. Executive functioning (EF) supports goal achievement and is associated with life success, and better outcomes following early life adversity. EF is also strongly related to processing speed, another predictor of life outcomes. Methods This longitudinal study examined 149 youths’ pre-pandemic EF and processing speed abilities as predictors of self-reported emotional, cognitive, and social experiences during the first year of the COVID-19 pandemic. EF and processing speed were measured with a total of 11 behavioral tasks. The COVID-era data was collected during two timepoints, during early (May-July 2020) and mid- (January-March of 2021) pandemic. Results Better pre-pandemic EF skills and processing speed abilities predicted more mid-COVID-19 pandemic emotional and cognitive difficulties. On the other hand, better switching (a subcomponent of EF) and processing speed abilities predicted more mid-pandemic social interactions. EF and processing speed abilities did not relate to the well-being reports from the initial months of the pandemic. Our EF - but not processing speed - results were largely maintained when controlling for pre-pandemic mental health burden, socioeconomic status (SES), and gender. Discussion Better cognitive abilities may have contributed to worse mid-pandemic functioning by supporting the meta-cognition needed for attending to the chaotic and ever-changing pandemic news and advice, leading to higher stress-induced worry and rumination. Our study highlights a potential downside of higher EF – often largely viewed as a protective factor - in youth.